Green growth and equity in the context of climate change: Some considerations - Jeffrey D. Sachs; Shiv Someshwar (Asian Development Bank Institute (ADBI), 2012)
Green growth entails several different kinds of processes: conversion to low-carbon energy, climate resilience, and response to climate shocks. Equity implies a fair sharing of the costs, within countries and between countries. The authors set out to explore some of the ways that equity has been considered in climate change discussions. They discuss per capita emission right approaches, and highlight key challenges in the application of equity in global climate change negotiations. They provide a brief overview key approaches to carbon financing, focusing on some recent cost estimations of potential climate change impacts, as well as of projected needs for green growth programs. The diversity of estimates and present evidence on the apparent gulf between available public financing and green growth needs are highlighted; and considerations of implementing green growth, focusing on building climate resilience and responding to climate shocks are discussed. In conclusion, the authors present one approach to a global Green Fund to receive assessed contributions of member countries and disburse grant and loan fund to low-income and middle-income countries to pursue green growth programs.
Keywords: Q2; Q5; 330; green growth; climate change; carbon financing; climate shocks; Wirtschaftswachstum; Nachhaltige Entwicklung; Klimawandel; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Umweltabkommen; Welt